2015
DOI: 10.1167/15.11.11
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual grouping via binocular disparity: The impact of stereoscopic good continuation

Abstract: Stereoscopic contextual effects are widely reported but are generally discussed in terms of 2-D Gestalt grouping principles, e.g., good continuation or closure. We propose that there are disparity-based grouping operations that are separable from 2-D grouping and instead depend on the distribution of binocular disparity information. Two experiments assess the impact of perceptual grouping via good disparity continuation. First, perceived depth magnitude is reduced for a multidot contour with a smooth disparity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 63 publications
6
11
0
Order By: Relevance
“…Recently, researchers have shown that the perception of quantitative depth in binocular stimuli depends upon surrounding disparity information, with the presence of continuous gradations in disparity resulting in a reduction in perceived depth (Cammack & Harris, 2016;Deas & Wilcox, 2014, 2015Hornsey, Hibbard, & Scarfe, 2016). These recent findings are consistent with much earlier results, which showed that disparity discrimination thresholds are increased for pairs of vertical lines when intervening horizontal lines create a closed figure (McKee, 1983;Mitchison & Westheimer, 1984).…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Recently, researchers have shown that the perception of quantitative depth in binocular stimuli depends upon surrounding disparity information, with the presence of continuous gradations in disparity resulting in a reduction in perceived depth (Cammack & Harris, 2016;Deas & Wilcox, 2014, 2015Hornsey, Hibbard, & Scarfe, 2016). These recent findings are consistent with much earlier results, which showed that disparity discrimination thresholds are increased for pairs of vertical lines when intervening horizontal lines create a closed figure (McKee, 1983;Mitchison & Westheimer, 1984).…”
Section: Introductionsupporting
confidence: 82%
“…To provide new insight into possible mechanisms governing surface-related reductions in perceived depth, this paper examines the interaction between factors of surface continuity (Cammack & Harris, 2016;Deas & Wilcox, 2014, 2015, considered in terms of the steepness of disparity variation across a stimulus, and surface discontinuity. Previous research on surface discontinuities has shown contradictory effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be interpreted as the consequence of combining conflicting evidence to the best segmentation of the image into distinct surfaces, rather than any direct effect on the way in which binocular disparity itself it processed. However, Gestalt grouping via closure also reduces the amount of depth that is perceived [34,35]…”
Section: Introductionmentioning
confidence: 99%
“…Beginning at V2, and continuing through multiple cortical sites, neurons show selectivity for relative disparities, that is, for differences between absolute disparity measurements across space (Fang et al, 2018;Neri, Bridge & Heeger, 2004;Thomas, Cumming & Parker, 2002;Umeda, Tanabe & Fujita, 2007). Although sensitivity for relative disparities has not been modeled extensively (cf., Assee & Qian 2007;Zhaoping, 2002), numerous psychophysical observations suggest the importance of processes operating at this level (e.g., Deas & Wilcox, 2014;Deas & Wilcox, 2015;Glennerster & McKee, 1999;Glennerster & McKee, 2004;Goutcher & Hibbard, 2010;Goutcher, Connolly & Hibbard, 2018;Goutcher & Wilcox, 2016;Vreven, McKee & Verghese, 2002;Wardle & Gillam 2016). Such results indicate that the tuning properties of relative disparity mechanisms are critically important for understanding the perception of cyclopean form (Goutcher et al, 2018;Hibbard, 2005;Tyler, 1975;Tyler, 2012;Tyler & Kontsevich, 2001).…”
Section: Introductionmentioning
confidence: 98%